The Role of ACE2 Receptors of the Olfactory System in Anosmia in COVID-19: An Overview - Mohammad Javad Nasr (Hindawi Limited, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the virus that causes coronavirus disease 2019 (COVID-19). The latest data show that more than 211.7 million people were infected and more than 4.4 million deaths have been reported. The illness presents a wide range of symptoms, ranging from mild to severe. Mild symptoms include cough, fever, dyspnea, fatigue, myalgia and arthralgia, anosmia, and dysgeusia. Furthermore, this virus can affect the central nervous system (CNS) and present a range of mild to severe nervous symptoms, from headache and dysphoria to loss of consciousness, coma, paralysis, and acute cerebrovascular disease. The virus can enter nonneuronal cells of the olfactory epithelium and cause a complete loss of smell. Anosmia and hyposmia are commonly reported in clinics, and being asymptomatic or showing mild symptoms can be primary symptoms in early infected persons. Dysgeusia/hypogeusia is another symptom presented with anosmia/hyposmia. In this article, we reviewed the articles of anosmia and suggested a possible mechanism for this.